FACTORS INFLUENCING SHALLOT FARMERS' DECISION TO ADOPT LIGHT TRAPS IN DEMAK, CENTRAL JAVA - Lia, Reza Siskana; Mukson, Mukson; Gayatri, Siwi; Anam, Mochammad Alawy Syaiful; Asror, Muhammad Zainul (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
The production of shallots in Demak district in 2019–2023 tends to decline and become less stable, mainly due to plant-disturbing organism attacks. Using chemical pesticides to deal with plant-disturbing organisms can damage soil and cause pest resistance, requiring environmentally friendly technologies such as insect light traps. In adopting light trap technology, it is interesting to study farmers' decision-making processes and the factors influencing them. We conducted the study in January 2024 in Demak District, Central Java, Indonesia, using survey and purposive sampling methods to identify factors influencing farmers' decision-making when using light trap technology to increase shallot productivity. The sample consisted of 165 farmers using light traps, with primary and secondary data. We used Smart-PLS 3.0 software to analyze the variable measurement using a Likert scale (1–5). With path coefficients of 0.460, 0.199, and 0.398, respectively, the study indicated that internal variables, external factors, and innovation features much influenced farmers' choice to adopt light trap technology. With a path coefficient of 0.649, light trap adoption favored agricultural productivity, hence driving a 42.1% rise in output. The model was generally good, with significant predictive power, with a GoF score of 0.65617 and an R-square value of 0.633. Therefore, this study accepts the hypotheses and finds that internal, external, and innovative aspects influence farmers' decision to utilize light traps. This study adds essential theoretical and empirical data and clarifies how smallholder farmers promote sustainable agriculture by using light traps, therefore lowering the usage of chemical pesticides.